Development Pengembangan AndroPhys sebagai Media Interaktif Berbasis Android untuk Meningkatkan Hasil Belajar Materi Momentum dan Impuls - Ryan Aryuansyah Artya Widodo (Jurnal Ilmu Fisika dan Pembelajarannya (JIFP), 2022)
The current Covid-19 situation has various impacts on human life. The education sector is no exception. The development of science as it is today is very fast where the internet and technology have become the main thing and are attached to society. This development is expected to be a new learning tool with this pandemic. The provision of learning media models that have never been taught in schools can improve the student's learning process to achieve the expectations desired by the teacher. So the researchers created an application called "AndroPhys" which can be applied in learning at school. The purpose of this research is to measure the validity, effectiveness, and practicality of the interactive media "AndroPhys" as a learning medium for student learning outcomes on momentum and impulse materials. This type of research is included in R&D with the ADDIE method. Based on the research stages that have been carried out, the validity of the "AndroPhys" application in the teaching and learning process is obtained with a percentage value of 90.30% with criteria that are said to be very feasible. The effectiveness of the "AndroPhys" application is said to be quite effective and the results of the implementation of learning achieved a percentage value of 94.44% so that it can be categorized as very good. From the results obtained this application can be said to be very practical. Through the results obtained, the "AndroPhys" application is appropriate to be used as an interactive medium for learning momentum and impulse materials in schools. Keyword: AndroPhys, Media, Learning, Momentum, Impulse